Direct effects of the resonant magnetic perturbation on turbulent transport. (29th July 2016) - Vlad, M.; Spineanu, F.
Abstract: The effects of the resonant magnetic perturbations (RMPs) on the turbulent transport are analyzed in the framework of the test particle approach using a semi-analytical method. The model includes particle collisions. The influence of the RMPs on plasma confinement is determined as function turbulence parameters and of collisionality. A synergy of the turbulent transport and RMPs is found. The increase of the turbulent diffusion is much larger than the diffusion directly produced by the RMPs.